ANALISIS STRATEGI PENGEMBANGAN LEMBAGA KEUANGAN MIKRO SYARIAH (LKMS) PEDESAAN (STUDI KASUS BMT AL HASANAH SEKAMPUNG) - Dedik Irawan; Muhamad Irfan Affandi; Umi Kalsum (Lampung University, 2013)
This research of analysis of the development strategy of Islamic microfinance institutions used SWOTanalysis. This study aimed to analyze the internal and external environmental conditions and alternativestrategies that can be applied in the development of Baitul Mal Wa TanWil (BMT) Al Hasanah Sekampung.The BMT internal environmental conditions showed that: 1) the level of education and skills of themanagement and employees were quite high and professionally, 2) the BMT has a strategic location, 3) theboards were very discipline, 4) the capital was used effectively, 5) product service very helpful members.Whereas, the five internal weaken factors were: 1) members who did not understand the concept of sharia, 2)the condition of the narrow building, 3) the administrative costs, 4) the capital owned cooperative was notgreat, 5), not all members could enjoy the service product. While the BMT external conditions were 1) theavailability of capital from third parties, 2) the BMT adopt profit-sharing system, 3) the governmentregulations that support BMT, 4) the majority of local merchants, 5) the online transfer technology, 6) mostof the capital third, 7) the increase of fuel prices, 8) the legislation government to the concept of sharia, 9)people did not understand the concept of Islamic and conventional, and 10) the cost of procurement. Basedon the three obtained priority strategies, the highest priority strategic alternatives were a) improve thequality of care, b) officers and employees had a high level of education, and c) the cooperation withgovernment and private agencies.